2014
DOI: 10.1055/s-0034-1377172
|View full text |Cite
|
Sign up to set email alerts
|

l-Menthol sprayed on gastric mucosa causes edematous change

Abstract: Background and study aims: l-Menthol (LM), sprayed on the distal gastric mucosa, is a safe antispasmodic agent used during esophagogastroduodenoscopy (EGD). However, it seems to affect gastric mucosal endoscopic findings. Therefore, we evaluated whether LM causes specific changes and impacts the endoscopic morphology of gastric lesions. Patients and methods: A total of 98 patients scheduled to undergo EGD were randomly assigned to receive LM solution (160 mg of 0.8 % LM added to 2.5 mL of indigo carmine [IC]; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…It is also likely that the same mechanism underlies the additional effectiveness of L -menthol in determining the tumor margin. Mori et al 14) reported that L -menthol application causes an edematous change of gastric mucosa and thereby clarifies the margin of gastric lesions, such as erosion, ulcer, and early stage cancer, which we have also demonstrated in a study using peppermint oil 6) .…”
Section: Discussionsupporting
confidence: 77%
“…It is also likely that the same mechanism underlies the additional effectiveness of L -menthol in determining the tumor margin. Mori et al 14) reported that L -menthol application causes an edematous change of gastric mucosa and thereby clarifies the margin of gastric lesions, such as erosion, ulcer, and early stage cancer, which we have also demonstrated in a study using peppermint oil 6) .…”
Section: Discussionsupporting
confidence: 77%
“…Because the gastric peristalsis was distinctly different from colorectal peristalsis, a subgroup analysis was conducted to differentiate the effects on the different types of peristalsis. Although there was no statistically significant difference between the 2 subgroups, the 2 colonoscopy studies ( 47 , 53 ) included in our meta-analysis showed a higher PNP and PNMP than the remaining 5 gastroscopy studies because the intestinal epithelial cells were the main absorption site for L-menthol ( 64 ) Similar result was found in a gastroscopy study which observed congestive more significant changes in the gastric mucosa of patients with atrophic gastritis after the administration of L-menthol than in patients without atrophy ( 46 ). A potential explanation for this finding is that atrophic gastritis is usually accompanied by intestinal metaplasia and contains some intestinal metaplasia cells that absorb L-menthol.…”
Section: Discussionsupporting
confidence: 73%
“…A low risk of selection bias was observed for 6 studies (6/8) because they used a computer ( 11 , 45 , 56 , 57 ) and randomization table ( 47 , 53 ) to generate the randomization code. Regarding allocation concealment, the majority of studies (5/8) ( 11 , 45 , 46 , 56 , 57 ) were deemed as displaying a low risk of bias due to the use of opaque sealed envelopes. In terms of attrition bias and reporting bias, no incomplete outcome data and selective reporting were identified in any of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations